Nanoparticle-modified chitosan-agarose-gelatin scaffold for sustained release of SDF-1 and BMP-2 - Wang, Bin (Int J Nanomedicine, 2018)
BACKGROUND: Stromal cell-derived factor 1 (SDF-1) is an important chemokine for stem cell mobilization, and plays a critical role in mobilization of mesenchymal stem cells (MSCs). Bone morphogenetic protein 2 (BMP-2) plays a critical role in osteogenesis of MSCs. However, the use of SDF-1 and BMP-2 in bone tissue engineering is limited by their short half-lives and rapid degradation in vitro and in vivo. METHODS: The chitosan oligosaccharide/heparin nanoparticles (CSO/H NPs) were first prepared via self-assembly. Chitosan-agarose-gelatin (CAG) Scaffolds were then synthesized via gelation technology using cross-linked chitosan, agarose, and gelatin, and were modified by CSO/H NPs. The encapsulation efficiency and release kinetics of SDF-1 and BMP-2 were quantified using an enzyme-linked immunosorbent assay. A CCK-8 assays were used to evaluate biocompatibility of NP-modified scaffolds. The biological activity of the loaded SDF-1 and BMP-2 was evaluated using the transwell migration assay and osteogenic induction assay. An animal MSC recruitment model was used to study the ability of SDF-1 released from NP-modified scaffolds to induce migration of MSCs. RESULTS: In this study, we developed a novel nanoparticle-modified CAG scaffold for the delivery of SDF-1 and BMP-2. CCK-8 assays demonstrated excellent biocompatibility of NP-modified scaffolds. In addition, we investigated the release of SDF-1 and BMP-2 from NP-modified scaffolds, and evaluated the effect of released SDF-1 on MSC migration. The effect of released BMP-2 on MSC osteogenesis was also examined. In vitro cell migration assays showed that SDF-1 released from NP-modified scaffolds retained its migration activity; osteogenesis studies demonstrated that released BMP-2 exhibited a strong ability to induce differentiation towards osteoblasts. Our in vivo recruitment assays showed continuous chemotactic response of MSCs to SDF-1 released from the NP-modified scaffold. CONCLUSION: The simplicity of synthesizing CSO/H NP-modified CAG scaffolds, combined with its high cytokine loading capacity and sustained release effect, renders NP-modified CAG scaffold an attractive candidate for sustained release of SDF-1 and BMP-2 to promote bone repair and regeneration.